Profile-measuring light probe using a change in reflection factor in the proximity of a critical angle of light - LEE; CHIA S (1988)
A profile-measuring light probe includes: an illuminator for irradiating a fine spot of light on a subject to be measured; an objective lens for forming an image of the fine spot on an image plane; and a relay lens for converting the light from the fine spot into a generally parallel ray. Further, the light probe includes a window plate constituted by an entrance prism for taking in the generally parallel ray emitted from the relay lens; a flat glass for subjecting the taken-in ray to multiple internal reflections and transmitting the same, and an exit prism for outputting the ray thus transmitted to the outside. The light probe measures the distribution of light quantity of the light emitted from the window plate to thereby measure a profile of the subject to be measured. With the above-described arrangement, it becomes possible for the light probe to perform the measuring through the utilization of a change in reflection factor of a light inciding in the proximity of a critical angle without using a critical angle prism.